CRITICAL DISCOURSE ON THE ROLE OF PROFESSIONAL COUNSELLORS IN INFLUENCING UNITY IN NIGERIA - EFE, Okarie; AKPEVWEOGHENE, Agamugoro, P. (Journal of Professional Counselling, 2025)
Nigeria faces a number of challenges, including increased corruption, lawlessness, instability, and disintegration. The involvement of professional counsellors is of paramount importance, especially during the formulation of policies aimed at promoting national integration. Recognizing this critical role, the present study explored how counsellors contribute to fostering unity in Nigeria. A descriptive survey design was utilized to systematically examine the research problem. The sampling procedure followed a multi-stage approach, beginning with stratification and culminating in purposive selection of 460 participants deemed relevant to the study objectives. Data collection was facilitated through a researcher-designed instrument, the Duties of Counsellors in Promoting Unity Questionnaire (DCPUQ), developed in alignment with the study constructs. Quantitative data were subjected to both descriptive statistical analysis and inferential testing using independent samples t-test. All statistical tests were conducted at a significance level of α = 0.05. Based on gender, level of education, and number of years of employment, the results showed a substantial variation in the role that counsellors had in fostering togetherness. It was suggested, based on the study's findings, that more school counsellors educate children about the importance of Nigerian unity and integration. Professional counselling services, especially advocacy visits/trips, be employed in helping to facilitate the unity of Nigeria. Female counsellors, counsellors with postgraduate qualification and with 20 years and above professional experience should be more involved in the advocacy of Nigeria’s unity in the course of their professional duties. Professional counsellors should legal framework and advocacy platform for national unity discourse. Counsellors are encouraged to engage in collaborative efforts with government agencies, nongovernmental organizations, and other relevant stakeholders to organize seminars and workshops that address contemporary issues pertaining to national integration and unity.